2014
DOI: 10.1103/physreve.89.053019
|View full text |Cite
|
Sign up to set email alerts
|

Elastic fingering in rotating Hele-Shaw flows

Abstract: The centrifugally driven viscous fingering problem arises when two immiscible fluids of different densities flow in a rotating Hele-Shaw cell. In this conventional setting an interplay between capillary and centrifugal forces makes the fluid-fluid interface unstable, leading to the formation of fingered structures that compete dynamically and reach different lengths. In this context, it is known that finger competition is very sensitive to changes in the viscosity contrast between the fluids. We study a varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The model also agrees with the experimental observations in the sense that a reactive system has destabilizing effect and the fingering instability is greater than that in a nonreactive system which is also confirmed in [15]. The elastic interface idea is also considered in a rotating Hele-Shaw flow [16,17]. In [17], the authors demonstrate a beautiful set of stationary morphologies depending on the competition between elastic and centrifugal forces.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The model also agrees with the experimental observations in the sense that a reactive system has destabilizing effect and the fingering instability is greater than that in a nonreactive system which is also confirmed in [15]. The elastic interface idea is also considered in a rotating Hele-Shaw flow [16,17]. In [17], the authors demonstrate a beautiful set of stationary morphologies depending on the competition between elastic and centrifugal forces.…”
Section: Introductionsupporting
confidence: 79%
“…To better elucidate the gains in efficiency using the rescaling scheme, we take a time dependent flux,Ĵ(t) = −105(37A 1 + A 2 ) 4R 3 (t) following Eq. (16). According to linear theory, this flux will lead the evolution to a 6-fold self-similar shape.…”
Section: Convergence Testmentioning
confidence: 99%
“…Besides the classical Hele-Shaw setup, there are several variants related to the viscous fingering problem [37,21,20,4,12,14,13,40]. For example, Hele-Shaw cells where the top plate is lifted uniformly at a prescribed speed and the bottom plate is fixed (lifting plate problem) [5,12,35,43,47,45,46] have been used to study adhesion related problems such as debonding [16,2,38,11] and the associated probe tack test [51,25].…”
Section: B1207mentioning
confidence: 99%
“…As in Refs. [20][21][22][23][24] we treat the interface as an elastic membrane, presenting a curvature-dependent bending rigidity as given by Eq. (2).…”
Section: Physical Problem and Governing Equationsmentioning
confidence: 99%
“…Later, Carvalho and coworkers [21] utilized the curvature-dependent bending rigidity model proposed in [20] to carry out a weakly nonlinear analysis of the system, and showed that when A = 0 nonlinear effects play a crucial role to determine the general shape assumed by the resulting patterned structures [21]. Subsequently, the same group of researchers investigated the manifestation of elastic fingering in rotating Hele-Shaw cells, where still unexploited pattern-forming dynamic behaviors [22], and innovative stationary morphologies [23] have been revealed as a result of the competition between elastic and centrifugal forces.…”
Section: Introductionmentioning
confidence: 99%